Evaluation of Synovex One Grower Implantation on Pre-weaning Performance of Suckling Beef Steers - Jonathan Jacquez (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: To evaluate the administration of Synovex One Grower (Zoetis,Parsippany, NJ) implants to suckling beef steer calves at approximately 50 days of age on pre-weaning growth performance. Study Description: Over three years, 306 spring-born suckling steer calves were randomly assigned to one of two treatments: 1) non-implanted control (CON) or 2) implanted with Synovex One Grower (IMP). Implants were administered at 49 ± 18 days of age and 194.0 ± 50.7 lb of body weight. Calves grazed on native mixed grass pastures with their dams until weaning at approximately 135 days of age. Calf average daily gain and total weight gain were determined. The Bottom Line: Administering Synovex One Grower implants to suckling beef steer calves at approximately 50 days of age improves pre-weaning performance during the early phase of hormone release.
Keywords: calf; gain; implant